(untitled) (Anclajes, 2012)
The constructive and thematic operations that Héctor Libertella exhibits in "The Legend of A. Pigafetta "(1985)," The story of Stories by Antonio Pigafetta "(1985) and The place that is not there (2006) articulate a practice of the caveman writer who adopts The first voyage around the World by Antonio Pigafetta as his own, rewrites it, and inserts it into other genealogies of Argentinean and Latin American literature. On the other hand, those operations exhibit a poetics that is part of a process in which reading, writing and literature reconcile and intermingle in a constant game of appropriations, transformations and displacements.